The Influence of Financial Technology and Service Features on Consumer Preferences for Choosing a Digital Wallet in Financial Transactions: (Study on OVO Application Users of UNISMA FIA Students Class of 2020) - Adinda Puspita Maharani; Sri Nuringwahyu; Ainul Chanafi (CV. Proaksara Global Transeduka, 2024)
The aim of this research is to investigate the impact of financial technology variables and service features on consumer choices when selecting digital wallets for financial transactions, utilizing a quantitative approach. Data collection was carried out through the use of questionnaires. The research population consisted of FIA students from the class of 2020 at UNISMA who are users of the OVO application. The results of the study reveal that consumer preferences (Y) are affected by financial technology variables (X1) and service features (X2). The F test results support the alternative hypothesis (Ha) and reject the null hypothesis (Ho), indicating that the independent variables have an influence on the dependent variable. The coefficient of determination shows an R square value of 0.299, suggesting that financial technology (X1) and service features (X2) collectively contribute to consumer preferences (Y) by 29.9%. Other variables not examined in this study account for 70.1% of the influence.